Sinon on his “pal” Palamedes (Virgil, Aeneid II 81-104) - Adkin, Neil (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
Sinon’s speech to the Trojans falsely represents him as Palamedes’ friend. The present article endeavours to show how in this connection Virgil avails himself of etymology.